Examining systemic steroid Use in older inflammatory bowel disease patients using hurdle models: a cohort study. Issue 1 (December 2015) - Johnson, Sophia; Palta, Mari; Bartels, Christie; Thorpe, Carolyn; Weiss, Jennifer; Smith, Maureen
Abstract Background Interpreting clinical guideline adherence and the appropriateness of medication regimens requires consideration of individual patient and caregiver factors. Factors leading to initiation of a medication may differ from those determining continued use. We believe this is the case for systemic steroid therapy in inflammatory bowel disease (IBD), resulting in a need to apply methods that separately consider factors associated with initiation and duration of therapy. To evaluate the relationship between patient characteristics and the frequency and duration of incident steroid use we apply a 2-part hurdle model to Medicare data. We do so in older patients with tumor necrosis factor antagonist (anti-TNFs) contraindications, as they are of special interest for compliance with Medicare-adopted, quality metrics calling for anti-TNFs and nonbiologic immune therapies to reduce steroid utilization. Many older patients have contraindications to anti-TNFs. However, nonbiologics cause adverse events that are concerning in older adults, limiting their use in this population and increasing reliance on systemic steroids. Methods We used a national Medicare sample for 2006–2009 including patients with 12 months or greater of Parts A and B and 6 months or greater of Part D coverage, IBD confirmed with at least 2 claims for ICD-9CM 555.xx or 556.xx, anti-TNF contraindications and without contraindications to nonbiologic agents. We applied a negative binomial-logit hurdle model to examine patient characteristics associated with systemic steroid utilization. Results Among the 1, 216 IBD patients without baseline steroid use, 21 % used systemic steroids. Odds of receiving systemic steroids were greater in those younger, rural, and those receiving other agents. Available patient characteristics failed to predict longer steroid treatment duration. Conclusions Our study identified differences in predictors of frequency and duration of medication use and suggests the utility of two-part models to examine drug utilization patterns. Applying such a model to Medicare data, we determined that despite medical consensus that systemic steroid use should be minimized, its use was substantial. Findings indicate anticipated difficulties in implementing recently adopted quality measures to avoid systemic steroids.